Secondary Health Care: best practices in the health services network La atención secundaria en salud: mejores prácticas en la red de servicios A atenção secundária em saúde: melhores práticas na rede de serviços - Alacoque Lorenzini Erdmann; Selma Regina de Andrade; Ana Lúcia Schaefer Ferreira de Mello; Livia Crespo Drago (Universidade de São Paulo, 2013)
OBJECTIVE: to understand the organization of health practices, based on the interactions at the secondary care level, and to analyze how the actions and services at this level of care contribute to the development of best practice in health. METHOD: a qualitative approach, based in Grounded Theory. Data was obtained from individual interviews, with managers, health care professionals and health service users making up the sample group representing the secondary level of healthcare. The theoretical model was formulated based on four categories, analyzed based in the elements of the network modeling of health care theoretical framework. RESULTS: The organization of health practices at a secondary level is in the process of consolidation and is contributing to the development of best practices in the locale studied. CONCLUSION: The broadening of access to consultations and specialized procedures, and the articulation of the network's points, are aspects of this level of care which are considered essential for care which is effective and integral. This study contributes to the analysis of health practices from the perspective of network modeling, based on the interactions between secondary care and the health system's other health facilities, which are shown as going through a process of consolidation in the locale studied. OBJETIVO: Comprender la organización de las prácticas de salud, desde las interacciones en el nivel de la atención secundaria y analizar cómo las acciones y servicios en este nivel han contribuido al desarrollo de mejores prácticas en salud. MÉTODO: Enfoque cualitativo, apoyado en la Teoría Fundamentada en los Datos. Se realizaron entrevistas con gestores, profesionales de salud y usuarios, que conforman el grupo muestral de la atención secundaria. RESULTADOS: Se formuló el modelo desde cuatro categorías, analizadas con base en los elementos del modelado de red de atención a la salud. La organización de las prácticas en el nivel secundario se encuentra en proceso de consolidación y ha contribuido al desarrollo de mejores prácticas en salud en el local estudiado. CONCLUSIÓN: La ampliación del acceso a consultas y procedimientos especializados y la articulación de puntos de la red son aspectos de este nivel considerados imprescindibles para la integralidad del cuidado. Este estudio contribuye para el análisis de las prácticas en salud en la perspectiva del modelado de red, desde las interacciones de la atención secundaria y los otros puntos del sistema de salud, que se presentan en proceso de consolidación en el contexto estudiado. OBJETIVO: compreender a organização das práticas de saúde, a partir das interações no nível da atenção secundária, e analisar como as ações e serviços nesse nível de atenção têm contribuido para o desenvolvimento de melhores práticas em saúde. MÉTODO: trata-se de abordagem qualitativa, apoiada no método da Teoria Fundamentada nos Dados. Os dados obtidos em entrevistas individuais, com gestores, profissionais de saúde e usuários, compôs o grupo amostral, representativo do nível de atenção secundária. Formulou-se o modelo teórico a partir de quatro categorias, analisadas com base nos elementos da modelagem de rede de atenção à saúde. RESULTADOS: a organização das práticas de saúde, no nível secundário, está em processo de consolidação e vem contribuindo para o desenvolvimento de melhores práticas em saúde no local estudado. CONCLUSÃO: a ampliação do acesso a consultas e procedimentos especializados e articulação dos pontos da rede são aspectos desse nível de atenção, considerados imprescindíveis para a resolubilidade e integralidade do cuidado. Este estudo contribui para a análise das práticas em saúde na perspectiva da modelagem de redes, a partir das interações da atenção secundária e dos demais pontos do sistema de saúde, que se mostram em processo de consolidação no local estudado.